Processing and characterisation of Boron-Titanium (B‐Ti) reactive materials - Ang, Wei An (2009)
This work investigates the synthesis of Boron‐Titanium (B‐Ti) reactive materials using two methods, namely a dry method – mechanical alloying and a wet method – suspension mixing. B‐Ti materials produced by these two methods were investigated by correlating their thermal properties and combustion kinetics with crystallographic and micro‐structural properties. One of the possible applications for this project includes development of high-energy density fuels.